Digital twin applications in athlete performance monitoring, biomechanical analysis, and injury prevention: implications for volleybal - Rudyanto Rudyanto; Vega Soniawan; Anisa Sholiha Mia (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Linking cyber-physical systems with top-level sports performance has presented digital twin (DT) as a competent instrument for optimizing athlete's performance and injury prevention. The current systematic literature review investigates how DTs have been applied in volleyball and other related sports. Using the PRISMA 2020 checklist, a search for relevant articles in Scopus and other databases resulted in 641 items dated 2020-2026. After exclusion of non-related articles and unscreened evaluation, only 8 papers were found to be suitable for the study. The outcomes highlighted three broad themes: (1) DT models for real-time injury risk prediction and biomechanical tracking, (2) individualized training and rehabilitation systems facilitating better load management and skill acquisition, and (3) comprehensive DT systems that use physiological, psychological and nutritional data to support the athlete more effectively. The bulk of the articles appeared post-2022, suggesting a quick increase of this research domain. In essence, DT technology seems highly capable of helping evidence-based coaching, athlete monitoring and injury prevention. However, more validation is still needed, particularly for cases coming from volleyball-specific situations.